การเปรียบเทียบการรับรู้ประสิทธิผลของหอผู้ป่วยระหว่างหัวหน้าหอผู้ป่วยกับพยาบาลประจำการ โรงพยาบาลมหาวิทยาลัยของรัฐ - แขวิมล ตันจริยานนท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
The purpose of this research was to compare patient unit effectiveness between 206 head nurses and 405 staff nurses which selected by multi-stage sampling. Research instruments were patient unit effectiveness of head nurse questionnaire and patient unit effectiveness of staff nurse questionnaire. These questionnaires were test for the content validity and reliability. The Cronbach s alpha coefficients of patient unit effectiveness for head nurses and patient unit effectiveness for staff nurses were .95 and .97 respectively. Statistical methods used for data analysis were mean, standard deviation and t-test. Major findings were as follows: 1. Mean score of patient unit effectiveness of head nurses, Governmental University Hospitals was at the high level (x-bar = 4.11). 2. Mean score of patient unit effectiveness of staff nurses, Governmental University Hospitals was at the high level (x-bar = 4.10). 3. There was no statistical difference between patient unit effectiveness as a whole as perceived by head nurses and staff nurses but in the satisfaction dimension there was statistical difference and significant at the .05 level (p<.05). 4. From focus group discussion head nurses suggested that organization culture should be the additional criteria to evaluate the unit effectiveness, while staff nurses suggested organization climate.